To what extent do disease severity and illness perceptions explain depression, anxiety and quality of life in hidradenitis suppurativa?. (1st February 2019) - Pavon Blanco, A.; Turner, M.A.; Petrof, G.; Weinman, J.
Summary: Background: Hidradenitis suppurativa (HS) can have significant psychological consequences and affect quality of life (QoL). This has been associated with disease severity. However, it has not been established whether these effects are more strongly related to the severity of the disease, as rated by the clinician, or to the patient's perception of their condition. Objectives: To examine the relationships between disease severity and illness perceptions, and depression, anxiety and QoL in HS. Methods: This study was cross‐sectional in design. In total, 211 patients with HS completed the Brief Illness Perception Questionnaire (BIPQ), the Patient's Health Questionnaire‐2 (PHQ‐2), the Generalized Anxiety Disorder‐2 (GAD‐2) and the Dermatology Life Quality Index (DLQI). HS severity was assessed by the clinician, using the Hurley staging system. Results: Patients with HS perceived their condition as chronic – having many symptoms, severe consequences and a negative emotional influence – and felt low personal control over their illness. Self‐reports showed significant levels of depression, anxiety and impaired QoL, which were strongly associated with illness perceptions. Hierarchical regression analyses revealed that illness perceptions explained a much greater proportion of variance in depression, anxiety and QoL than the traditional explanatory variable, disease severity. Conclusions: HS can severely impair psychological well‐being and QoL, which are more strongly associated with the person's beliefs about their illness than clinicians' severity assessments. Therefore, illness perceptions may be useful in the routine assessment of patients with HS and may provide a strong basis for interventions aimed at improving their psychological well‐being and QoL.